STUDY OF THE INFLUENCE OF THE COMPOSITION OF CULTURAL MEDIUM ON THE BASIS OF A WHITE CABBAGE ON DEVELOPMENT OF LEUCONOSTOC MESENTEROIDES AT THE PRE-FERMENTATION STAGE - V. V. Kondratenko; O. Yu. Lyalina; N. E. Posokina; A. Yu. Kolokolova; V. I. Tereshonok (Овощи России, 2018)
The aim of the research was to study the regularity of the influence of the culture medium (substrate) on the development of microflora on the pre -fermentation stage of a model medium made from white cabbage «Parus», using strains of lactic acid microorganisms Leuconostoc mesenteroides VKPM B-8818. The main task in the research process was to perform a stepby-step mathematical processing of experimental data and analyze them, to obtain functional dependencies adequately approximating the experimental data for the base (BMS) and modified (MMC) model media. Analysis of the experimental data showed that, depending on the type (composition) of the medium, the same species of microorganisms exhibit different dynamics of titer growth. In connection with this, an algorithm was developed to determine the optimal duration of pre-fermentation – «stop points». The results of the research showed that modification of the model medium with the addition of table salt and ascorbic acid to it promotes the formation of positive dynamics of the comparison indicator. This dynamics has three extreme extremes, but only extremes are of practical significance, which are in the interval of the monotonic decrease of the titer. One of the conditions for successful development of the starting culture at the main stage of fermentation is a relatively small amount of the first culture's titer at the end of the preliminary fermentation stage in order to exclude competition. Consequently, the position of the "stoppoint" corresponds to the period after the last peak of the comparison indicator. These studies on the regularity of the effect of the pre-cultivation of gram-positive microorganisms on the activity of lactic acid microorganisms in the process of fermentation are relevant, since the whole process and the production of high-quality products depend on this approach in full.